Bardoxolone methyl analog attenuates proteinuria‐induced tubular damage by modulating mitochondrial function. Issue 11 (30th August 2019) - Nagasu, Hajime; Sogawa, Yuji; Kidokoro, Kengo; Itano, Seiji; Yamamoto, Toshiya; Satoh, Minoru; Sasaki, Tamaki; Suzuki, Takafumi; Yamamoto, Masayuki; Wigley, W. Christian; Proksch, Joel W.; Meyer, Colin J.; et al.
Abstract : Multiple clinical studies have shown that bardoxolone methyl, a potent activator of nuclear factor erythroid 2‐related factor 2 (Nrf2), is effective in increasing glomerular filtration rate in patients with chronic kidney disease. However, whether an Nrf2 activator can protect tubules from proteinuria‐induced tubular damage via anti‐inflammatory and antioxidative stress mechanisms is unknown. Using an Institute of Cancer Research‐derived glomerulonephritis (ICGN) mouse model of nephrosis, we examined the effects of dihydro‐CDDO‐trifluoroethyl amide (dh404), a rodent‐tolerable bardoxolone methyl analog, in protecting the tubulointerstitium; dh404 markedly suppressed tubular epithelial cell damage in the renal interstitium of ICGN mice. The tubular epithelial cells of ICGN mice showed a decrease in the size and number of mitochondria, as well as the breakdown of the crista structure, whereas the number and ultrastructure of mitochondria were maintained by the dh404 treatment. To further determine the effect of dh404 on mitochondrial function, we used human proximal tubular cells in vitro. Stimulation with albumin and free fatty acid increased mitochondrial reactive oxygen species (ROS). However, dh404 administration diminished mitochondrial ROS. Our data show that dh404 significantly reduced proteinuria‐induced tubular cell mitochondrial damage, suggesting that improved redox balance and mitochondrial function and suppression of inflammation underlie the cytoprotective mechanism of Nrf2 activators, including bardoxolone methyl, in diabetic kidney disease.—Nagasu, H., Sogawa, Y., Kidokoro, K., Itano, S., Yamamoto, T., Satoh, M., Sasaki, T., Suzuki, T., Yamamoto, M., Wigley, W. C., Proksch, J. W., Meyer, C. J., Kashihara, N. Bardoxolone methyl analog attenuates proteinuria‐induced tubular damage by modulating mitochondrial function. FASEB J. 33, 12253‐12263 (2019). www.fasebj.org